1992
DOI: 10.1121/1.402772
|View full text |Cite
|
Sign up to set email alerts
|

The role of frequency selectivity in measures of auditory and vibrotactile temporal resolution

Abstract: The purpose of this study was to compare the role of frequency selectivity in measures of auditory and vibrotactile temporal resolution. In the first experiment, temporal modulation transfer functions for a sinusoidally amplitude modulated (SAM) 250-Hz carrier revealed auditory modulation thresholds significantly lower than corresponding vibrotactile modulation thresholds at SAM frequencies greater than or equal to 100 Hz. In the second experiment, auditory and vibrotactile gap detection thresholds were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 0 publications
6
18
1
Order By: Relevance
“…The data of Formby et al (1992Formby et al ( , 1998 for monaural 250-Hz conditions indicate an increase in the GDT from roughly 7 ms for their 250-250 Hz condition to roughly 25-30 ms for their 250-375 Hz condition, consistent with our young NH results shown in Fig. 1.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The data of Formby et al (1992Formby et al ( , 1998 for monaural 250-Hz conditions indicate an increase in the GDT from roughly 7 ms for their 250-250 Hz condition to roughly 25-30 ms for their 250-375 Hz condition, consistent with our young NH results shown in Fig. 1.…”
Section: Discussionsupporting
confidence: 80%
“…The AGDDTs obtained for young NH listeners were consistent with those reported by Formby et al (1992Formby et al ( , 1998 using a 250-Hz leading marker and trailing markers in the range of 250 to 500 Hz. The data of Formby et al (1992Formby et al ( , 1998 for monaural 250-Hz conditions indicate an increase in the GDT from roughly 7 ms for their 250-250 Hz condition to roughly 25-30 ms for their 250-375 Hz condition, consistent with our young NH results shown in Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, despite the abundance of studies on this sensory channel, few have investigated its ability to convey information about nonsinusoidal waveforms (see Bensmaïa & Hollins, 2000;Formby, Morgan, Forrest, & Raney, 1992;Horch, 1991;Lamoré, Muijser, & Keemink, 1986;Morley, Archer, Ferrington, Rowe, & Turman, 1990;Weisenberger, 1986). In a previous study (Bensmaïa & Hollins, 2000), we found that subjects could not use Pacinian signals to discriminate between diharmonic stimuli that differed only in the phase angle of the high-frequency component with respect to the low-frequency component.…”
mentioning
confidence: 99%